Functional evaluation of oral rehabilitation with removable partial dentures after five years Avaliação funcional da reabilitação oral com prótese parcial removível após cinco anos - Dúcia Caldas Cosme; Simone Michielon Baldisserotto; Eduardo de Lima Fernandes; Elken Gomes Rivaldo; Cassiano Kuchenbecker Rosing; Rosemary Sadami Arai Shinkai (University of São Paulo, 2006)
Most removable partial denture (RPD) wearers are satisfied with their prostheses, but the factors that influence satisfaction and acceptance are still not determined. OBJECTIVE: This study explored technical, biological, and satisfaction variables for the functioning of RPDs after five years, and compared the evaluation by the patient and by the clinician. MATERIAL AND METHODS: Fifty adults (39 females, 11 males) were re-examined after five years of RPD service. Data were collected through clinical examination and a structured questionnaire to record the conditions of supporting soft tissues, prosthesis acceptance and technical characteristics, mastication, esthetics, comfort, hygiene, and need for professional intervention. Data were analyzed by descriptive statistics and Spearman correlation. RESULTS: More than 50% of patients classified their RPDs as excellent regarding retention, mastication, esthetics, comfort, and hygiene. In the professional evaluation, retention and stability were considered excellent in more than 66% of cases, and hygiene of teeth and prostheses was considered good in 52% and 46%, respectively. The metallic framework and acrylic base were considered adapted in 92% of cases. Prosthesis acceptance was associated with retention, mastication, esthetics, hygiene, and comfort evaluated by the patient, and with retention, stability, and condition of the framework evaluated by the clinician. Retention and mastication/comfort evaluated by the patient had moderate positive correlation with retention and stability measured by the clinician. There was no association of hygiene evaluation by the patient and by the clinician. CONCLUSIONS: After five years, the oral rehabilitation with RPDs was satisfactory for most cases. There was correspondence between retention/retention and mastication-comfort/stability variables evaluated by the patient and by the clinician. Oral and prosthesis hygiene were not related. A maioria dos usuários de PPR mostra-se satisfeita com suas próteses, porém os fatores que influenciam a satisfação e aceitação não estão determinados. OBJETIVO: Este estudo explorou variáveis técnicas, biológicas e de satisfação no funcionamento de próteses parciais removíveis (PPRs) após cinco anos de uso, comparando a avaliação do paciente e do cirurgião-dentista. MATERIAIS E MÉTODOS: Cinqüenta adultos (39 mulheres, 11 homens) foram reexaminados após cinco anos da instalação de PPR. Através de exame clínico e questionário estruturado, foram coletados os dados relativos às condições dos tecidos de suporte, aceitação e características técnicas da PPR, mastigação, estética, conforto, higiene e necessidade de intervenção profissional. Os dados foram analisados por estatística descritiva e por correlação de Spearman. RESULTADOS: Mais de 50% dos pacientes classificaram suas próteses como excelente quanto à retenção, mastigação, estética, conforto e higiene. Na avaliação do profissional, retenção e estabilidade foram consideradas excelentes em mais de 66% dos pacientes, e a higiene dos dentes e da prótese foi considerada boa em 52% e 46% dos casos, respectivamente. As armações metálicas e bases acrílicas foram consideradas adaptadas em 92% dos casos. Aceitação da prótese foi associada com retenção, mastigação, estética, higiene e conforto avaliados pelo paciente, e com retenção, estabilidade e condição da armação metálica avaliadas pelo profissional. Retenção e mastigação/conforto, avaliados pelo paciente, mostraram correlação positiva moderada com retenção e estabilidade medidas pelo profissional. Não houve associação entre avaliação de higiene pelo paciente e pelo profissional. CONCLUSÕES: Após cinco anos, a reabilitação oral com PPR estava satisfatória na maioria dos casos. Houve correspondência entre as variáveis retenção/retenção e mastigação-conforto/estabilidade. Higiene oral e da prótese não mostraram associação.